Pengaruh Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Melalui Penempatan Kerja Sebagai Variabel Intervening (Studi Pada PT. BPD Kaltim-Kaltara Kantor Cabang Tenggarong) - Islami, Irfioni Cornely; Sari, Nilam Anggar; Mawardi, Mawardi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
The problem that occurred at PT. BPD Kaltim-Kaltara Tenggarong Branch Office that there are still many customers waiting for service queues with a long duration of time, although it is undeniable that employees has implemented the existing procedures in the company effectively and efficiently. The purpose of this study was to identify and examine the effect of recruitment and selection on employee performance through job placement as an intervening variable. Data collection was carried out by distributing questionnaires to employees of PT. BPD Kaltim-Kaltara Tenggarong Branch Office, totaling 68 respondents. This study uses quantitative methods with census techniques. The data obtained was then processed using a structural equation model (SEM PLS 4). The results showed that (1) recruitment did not affect performance (2) recruitment did not affect job placement (3) selection had an effect on performance (4) selection had no effect on job placement (5) job placement had no effect on performance (6) recruitment does not affect performance through job placement (7) selection does not affect performance through placement.